2009
DOI: 10.1002/jmv.21532
|View full text |Cite
|
Sign up to set email alerts
|

IgA antibodies against the Epstein‐Barr nuclear antigen1 as a valuable biomarker for the diagnosis of nasopharyngeal carcinoma in Tunisian patients

Abstract: Serological tests for Epstein-Barr virus (EBV) have been used for many years as diagnostic predictors of nasopharyngeal carcinoma. It has been shown previously that the conventional immunofluorescence assay has a limited diagnostic value, especially in young patients from North African area. In the search for more reliable immunoglobulin (Ig) G or IgA antibody markers for the diagnosis of nasopharyngeal carcinoma, immunoblot analysis was performed using a full spectrum of EBV proteins. Sera were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Among distinct biologic features in young patients with NPC are higher levels of EBV latent membrane protein expression 13, lower levels of the antiapoptotic BCL‐2 expression 14, and greater c‐KIT protein expression. Furthermore, young patients had lower IgA antibody responses against ZEBRA ( P < 0.01), VCA‐p40 ( P = 0.05), and EA‐p47/54 ( P = 0.04) antigens 15. On the other hand, there does not seem to be a viral polymorphism more consistently associated with juvenile or adult NPC 16.…”
Section: Discussionmentioning
confidence: 93%
“…Among distinct biologic features in young patients with NPC are higher levels of EBV latent membrane protein expression 13, lower levels of the antiapoptotic BCL‐2 expression 14, and greater c‐KIT protein expression. Furthermore, young patients had lower IgA antibody responses against ZEBRA ( P < 0.01), VCA‐p40 ( P = 0.05), and EA‐p47/54 ( P = 0.04) antigens 15. On the other hand, there does not seem to be a viral polymorphism more consistently associated with juvenile or adult NPC 16.…”
Section: Discussionmentioning
confidence: 93%
“…In 1973, presence of EBV genomes was demonstrated in epithelial NPC cells [18] and EBV-related antigens were detected in the tumor cells of all NPC patients [26]. Subsequently, the expression of the viral genome in non-keratinising NPC has been studied extensively in areas with NPC epidemic [14], [16], [27] and major types of viral expression proteins have been found, e.g., EBNA1 [28][30], LMP1 [15], [31]–[34] and LMP2A [31]. Moreover, in case-control studies, NPC cases showed significantly higher antibody titers to EBV antigens than controls in several retrospective studies [11], [19], [35][38].…”
Section: Introductionmentioning
confidence: 99%
“…The association of a viral infection and the initiation of certain types of cancer makes the detection of viral nucleic acids an interesting potential method. There are several pieces of evidence for the presence of Epstein-Barr virus (EBV) DNA in the blood of nasopharyngeal carcinoma patients [59,60] and for the presence of Human Papilloma virus (HPV) DNA in patients with cervical cancer [61] or head and neck squamous cell carcinoma [62].…”
Section: Cancer Diagnosticsmentioning
confidence: 99%